2019
DOI: 10.3390/jcm8101691
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological Symptoms and Gaming Motives in Disordered Gaming—A Psychometric Comparison between the WHO and APA Diagnostic Frameworks

Abstract: Background: ‘Gaming Disorder’ (GD) has received increased medical attention and official recognition from both the American Psychiatric Association (APA) and the World Health Organization (WHO). Although these two medical organizations have independently developed promising clinical diagnostic frameworks to assess disordered gaming, little is known about how these frameworks compare at different psychometric levels in terms of producing consistent outcomes in the assessment of GD. Methods: A sample of 1429 Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
98
4
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 70 publications
16
98
4
6
Order By: Relevance
“…These discrepancies may be due to the use of different psychometric tools in assessing IGD. In other studies that have utilized the IGDS9-SF, the prevalence rates of disordered gaming were reported to be between 3% to 5% [59,61]. The results of the present study fall within the prevalence rate range reported by other international studies [31].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These discrepancies may be due to the use of different psychometric tools in assessing IGD. In other studies that have utilized the IGDS9-SF, the prevalence rates of disordered gaming were reported to be between 3% to 5% [59,61]. The results of the present study fall within the prevalence rate range reported by other international studies [31].…”
Section: Discussionsupporting
confidence: 81%
“…The secondary objectives of this study were to: (a) to obtain indicators of validity and reliability of the Spanish version of IGDS9-SF, including the confirmatory study of its factor structure; (b) to test whether the newly developed psychometric test works equally in both men and women, as well as in adolescences and young adults; (c) establish the prevalence of IGD in a sample of adolescents and young Vocational Training (VT) students aged between 15 and 25 years; and (d) examine the relationship between the IGD and HRQoL. To achieve the aforementioned objective, it was hypothesized that: (i) the IGDS9-SF would show adequate psychometric properties in the sample recruited, similarly to previous IGDS9-SF psychometric validation studies conducted in different countries [58,59,61,67]; (ii) the measurement model would be invariant across both genders [57]; (iii) the prevalence of IGD would be between 2% and 4%, which is referred to in other national and international studies [27,37]; and (iv) those who met the IGD criteria within the sample recruited would present lower scores on the different HRQoL dimensions [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to ICD-11, symptoms and disability aspects need to be present both for the diagnosis to be fulfilled. This underlines the different conceptualization and diagnostic approach of the ICD-11 compared to the DSM-5 [20]. In their recent review King and colleagues (2020) identified 32 IGD assessment tools available in the English language and employed in 320 studies [19].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion in the diagnostic classification systems takes account of the growing concerns with respect to detrimental mental health effects of excessive and in some cases compulsive engagement in Internet gaming. Prevalence estimates of Internet Gaming Disorder (IGD) range from 0.3%-27.5% worldwide 3 with a recent representative survey suggesting that 1.16% of adolescents in Germany meet the diagnostic criteria for IGD according to DSM-5 criteria 4 (prevalence estimates according to the WHO criteria see [5]). Accumulating evidence from cross-sectional .…”
Section: Introductionmentioning
confidence: 99%